2002
DOI: 10.1016/s1567-1356(02)00082-x
|View full text |Cite
|
Sign up to set email alerts
|

Protein expression and secretion in the yeast

Abstract: Strains and vectors for protein expression and secretion have been developed in the yeast Yarrowia lipolytica. Host strains were constructed with non-reverting auxotrophic markers, deletions of protease-encoding genes, and carrying a docking platform. To drive transcription, either the synthetic hp4d or the inducible POX2 promoter were used. Protein secretion is either directed by the targeting sequence of the alkaline extracellular protease or the extracellular lipase (LIP2p) signal sequence. We describe a se… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
105
0
1

Year Published

2004
2004
2022
2022

Publication Types

Select...
6
1
1

Relationship

0
8

Authors

Journals

citations
Cited by 116 publications
(107 citation statements)
references
References 21 publications
1
105
0
1
Order By: Relevance
“…According to the characteristics provided by Madzak et al (2004), hp4d recombinant promoter is almost independent from environmental conditions and is able to drive a strong expression in virtually any medium, promoting growth-phase-dependent gene expression. It was found that hp4d-driven heterologous gene expression occurs mostly at the beginning of the stationary phase (Nicaud et al 2002), which we have also observed in our study. However, the increase in the pH value obviously hampered further accumulation of the recombinant α-amylase.…”
Section: Discussionsupporting
confidence: 90%
See 2 more Smart Citations
“…According to the characteristics provided by Madzak et al (2004), hp4d recombinant promoter is almost independent from environmental conditions and is able to drive a strong expression in virtually any medium, promoting growth-phase-dependent gene expression. It was found that hp4d-driven heterologous gene expression occurs mostly at the beginning of the stationary phase (Nicaud et al 2002), which we have also observed in our study. However, the increase in the pH value obviously hampered further accumulation of the recombinant α-amylase.…”
Section: Discussionsupporting
confidence: 90%
“…As demonstrated by Nicaud et al (2002), the heterologous gene copy number was a strong determinant of the amount of an enzyme produced, contributing to up to 8-fold increase in the enzyme activity, solely due to gene amplification. The technique applied in this study indicated the presence of 4 copies of the Amy1 gene per genome of Y. lipolytica 1.18 strain.…”
Section: Discussionmentioning
confidence: 87%
See 1 more Smart Citation
“…The auxotrophic strain Po1f (Leu − , Ura − ) and Po1g (Leu − ) derived from the wild type strain W29 (ATCC 20460) were kindly provided by Professor Catherine Madzak (Institut National de la Recherche Agronomique, AgroParisTech, France) [42, 43]. Po1f was used as a recipient of strain engineering and Po1g was used as the control strain.…”
Section: Methodsmentioning
confidence: 99%
“…Além disso, excreta várias enzimas, como proteases, lipases, esterases e fosfatases, todas de grande interesse biotecnológico (Nicaud et al, 2002).…”
Section: Introductionunclassified